From electronic structure to phase diagrams: A bottom-up approach to understand the stability of titanium–transition metal alloys. (July 2016) - Huang, Liang-Feng; Grabowski, Blazej; Zhang, Jian; Lai, Min-Jie; Tasan, C. Cem; Sandlöbes, Stefanie; Raabe, Dierk; Neugebauer, Jörg
Abstract: We have computed formation energies for all technologically relevant transition metal solutes in the α, β, and ω phases of Ti, employing ab initio simulations. We analyze and explain their periodic-table trends, and from their differences we derive stabilization energies which provide direct insight into phase stabilization effects of the various solutes with respect to α, β, and ω . This allows us to identify strong β stabilizers in the middle of each electronic d shell in consistency with experimental knowledge. Based on an extension of the stabilization energies to free energies we derive a wide range of Ti-transition metal phase diagrams. A detailed comparison to available experimental martensitic transformation temperatures and to measurements performed in this study shows that, despite some quantitative discrepancies, the qualitative trends can be expected to be correct. An important feature that is displayed by a limited range of the computed phase diagrams is a triple point at which the three phases, α, β, and ω, meet. This insight provides a plausible explanation for the complexity observed in gum metals, a class of Ti alloys with very special materials properties. Graphical abstract: